2017
DOI: 10.1080/13548506.2017.1363395
|View full text |Cite
|
Sign up to set email alerts
|

Resisting temptation: alcohol specific self-efficacy mediates the impacts of compensatory health beliefs and behaviours on alcohol consumption

Abstract: Awareness of health risks linked with excessive alcohol consumption appears to have little influence on how much some people drink. Compensatory health beliefs (CHBs), in which the consequences of unhealthy behaviour are considered to be neutralised by additional healthy behaviours, are one way of justifying poor health choices. Currently, the role of CHBs within the context of drinking behaviour is not well understood. This research examined associations between alcohol specific compensatory health beliefs (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…Though no previous work on CHB addressed breastfeeding, studies on other health behaviors provide ample empirical evidence of holding CHB as a means of ameliorating cognitive discomfort in various situations. For example, smoking-specific CHBs were found to be significantly negatively related to the intention to stop smoking [ 24 ]; alcohol-specific CHB were associated with an increase in alcohol consumption [ 26 ]; and post-exercise beliefs licensing the consumption of unhealthy snacks were higher among people driven by control motivation (rather than by autonomy) [ 35 ]. In the context of breastfeeding, our findings indicate that women who do not breastfeed (or do not do so exclusively) hold more CHBs, suggesting an attempt to resolve the contradiction between how they view themselves as mothers and the normative social portrayal of breastfeeding, which was probably partially internalized.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Though no previous work on CHB addressed breastfeeding, studies on other health behaviors provide ample empirical evidence of holding CHB as a means of ameliorating cognitive discomfort in various situations. For example, smoking-specific CHBs were found to be significantly negatively related to the intention to stop smoking [ 24 ]; alcohol-specific CHB were associated with an increase in alcohol consumption [ 26 ]; and post-exercise beliefs licensing the consumption of unhealthy snacks were higher among people driven by control motivation (rather than by autonomy) [ 35 ]. In the context of breastfeeding, our findings indicate that women who do not breastfeed (or do not do so exclusively) hold more CHBs, suggesting an attempt to resolve the contradiction between how they view themselves as mothers and the normative social portrayal of breastfeeding, which was probably partially internalized.…”
Section: Discussionmentioning
confidence: 99%
“…Nor was the possibility of compensatory behavior (in relation to non-breastfeeding) [ 24 ] examined; for example, whether non-breastfeeding mothers spend more time with their babies. Related antecedents or moderators, examined in other studies in more oft-researched areas, were also not addressed: For example, whether self-efficacy in breastfeeding [ 20 , 26 ] is associated with CHB. Lastly, the data collection method—the online convenience survey—resulted in a non-representative sample of Israeli birth-giving women, specifically this sample was more affluent and more educated than the population of women of this age group in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaklamanou et al (2013) suggested to include a time dimension on CHBs scales, to target the behaviour rather than the belief itself, and that items should be phrased at the first person. Our scale is derived from these recommendations, and from recent measures of CHBs (e.g., Matley & Davies, 2017). Rather than focusing on frequency of healthy behaviours, our scale focuses on the unhealthy behaviours adoption frequency, and considers thus the behaviouralsub-dimension of the CHBs more than the belief in the compensatory effect itself.…”
Section: Methodsmentioning
confidence: 99%
“…CHBs may negatively contribute to the intention formation process, independently from behaviour-specific factors (self-efficacy, risk perceptions, outcome expectancies) (Berli, Loretini, Radtke, Hornung, & Scholz, 2014;Fleig et al, 2015;Radtke, Scholz, Keller, & Hornung, 2012), and through the self-efficacy mediating role (Matley & Davies, 2017). CHBs may also interact with self-efficacy (they negatively predict intention when self-efficacy is low, Storm et al, 2016) and risk perception (they positively predict intention when risk perception is high, Radtke, Kaklamanou, Scholz, Hornung, & Armitage, 2014).…”
Section: Introductionmentioning
confidence: 99%